ELECTRONIC CITATION IN THE BRAZILIAN CIVIL PROCEDURE CODE - Roberto Hertel, Daniel (2026)
Deals with electronic citation in the Code of Civil Procedure. It addresses the various aspects related to the referred modality of citation, inserted by the Legislator of Law n. 14.195/21. It clarifies that electronic citation is now adopted as the preferred modality, also mentioning the people who can be cited electronically. Tools for electronic citation were also addressed, as well as aspects related to the validity of electronic citation and the possibility of applying the effects of default. The procedural deadlines related to electronic citation and its application in the knowledge and enforcement processes were addressed, as well as in the sentence fulfillment phase, when the need for citation of the debtor is required by the Legislator.